The Dynamics of Sea Tide-Induced Fluctuations of Groundwater Level and Freshwater-Saltwater Interface in Coastal Aquifers: Laboratory Experiments and Numerical Modeling. (5th August 2019) - Levanon, Elad; Gvirtzman, Haim; Yechieli, Yoseph; Oz, Imri; Ben-Zur, Elad; Shalev, Eyal
Abstract : Laboratory experiments were conducted in a vertical, two-dimensional, rectangular flow tank, simulating the response of a phreatic coastal aquifer to a sea tide. Imposed sinusoidal fluctuations of the saltwater level at one side of the flow tank caused three types of fluctuations: (a) hydraulic head throughout the aquifer, (b) saturation degree within the capillary fringe, and (c) salt concentration surrounding the freshwater-saltwater interface (FSI), all recorded by head, saturation, and salinity sensors, respectively. Significant time lags were observed both in the saturation degree within the unsaturated zone and in the salinity within the FSI. All measured values, recorded by the three types of sensors, were simulated and reproduced using a numerical model. The calibrated model was used for mapping the time lags throughout the aquifer. It was found that the time lag of saturation fluctuations within the unsaturated zone increased upward from the groundwater level as the unsaturated hydraulic conductivity decreased. Similarly, the time lag of salinity fluctuations within the FSI increased downward, with distance from the groundwater level. We interpret the low hydraulic conductivity at the capillary zone as the source of attenuation of both saturation and salinity, because both are controlled by the vertical advection of the whole freshwater body. This advection is significantly slower compared to the dynamics of pressure diffusion. The uniqueness of this study is that it provides quantitative data on the attenuation at the capillary zone and its effect on the salinity time lag in coastal aquifer systems.